2022
DOI: 10.3390/molecules27144370
|View full text |Cite
|
Sign up to set email alerts
|

Nitriles with High Gas-Phase Basicity—Part II Transmission of the Push–Pull Effect through Methylenecyclopropene and Cyclopropenimine Scaffolds Intercalated between Different Electron Donor(s) and the Cyano N-Protonation Site

Abstract: This work extends our earlier quantum chemical studies on the gas-phase basicity of very strong N-bases to two series of nitriles containing the methylenecyclopropene and cyclopropenimine scaffolds with dissymmetrical substitution by one or two electron-donating substituents such as Me, NR2, N=C (NR2)2, and N=P (NR2)3, the last three being strong donors. For a proper prediction of their gas-phase base properties, all potential isomeric phenomena and reasonable potential protonation sites are considered to avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Gauss View 5 software was used to visualize the output files [21]. The structural properties of compounds 1a-c and 2a-c were determined by applying Becke's threeparameter hybrid functional (B3) for the exchange part and the Lee-Yang-Parr (LYP) correlation function [22] with 6-31G(d,p) level in order to obtain the optimized geometrical parameters of the compound. The MEP and HOMO-LUMO energies were calculated at the same level.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…Gauss View 5 software was used to visualize the output files [21]. The structural properties of compounds 1a-c and 2a-c were determined by applying Becke's threeparameter hybrid functional (B3) for the exchange part and the Lee-Yang-Parr (LYP) correlation function [22] with 6-31G(d,p) level in order to obtain the optimized geometrical parameters of the compound. The MEP and HOMO-LUMO energies were calculated at the same level.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…The relative quantities (∆E, ∆H, T∆S, and ∆G) have been calculated separately for ionic isomers of mono-anions (ABH) − , di-anions (AB) 2− , mono-cations (AH 2 BH) + , and di-cations (AH 2 BH 2 ) 2+ . The composition of the neutral and ionic isomeric mixtures of C and iC have be estimated on the basis of ∆G i calculated for individual neutral and ionic isomers using equation (1), where x i is the isomer mole-fraction [51][52][53][54]. Note that ∆G i can be different for neutral and ionic isomers, and thus the calculated x i cannot be the same for ionic and neutral species.…”
Section: Methodsmentioning
confidence: 99%
“…Isomeric (rotational and/or prototropic) states of neutral and protonated forms and also the favored sites of protonation in the other derivatives given in Figure 3 ( HA , Agm , AEP , FDMEP , BG , M , I , and nitriles) have been analyzed by us at various DFT and/or MP2 levels over the last 20 years [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. For HA , AEP , and FDMEP , their GB values were also determined by FT-ICR equilibrium measurements (960.3, 954.8, and 1008.8 kJ mol −1 , respectively, evaluated in Ref.…”
Section: Theoretical Treatment Of Isomeric Basesmentioning
confidence: 99%
“…The experimental GBs of Me 2 N–CH=N–C≡N (857.3 kJ mol −1 ) and Me 2 N–CH=CH–C≡N (864.3 kJ mol −1 ) are higher than that of NH 3 (819.0 kJ mol −1 ) but close to that of MeNH 2 (864.5 kJ mol −1 ) [ 9 ]. On the other hand, detailed theoretical studies for various series of push–pull nitriles with guanidino and phosphazeno groups linked directly to the cyano-C atom or separated by a resonance transmitter indicated that it is possible to extend the GB scale for nitriles up to 1100 kJ mol −1 [ 74 , 75 , 100 , 101 ]. The calculated strong electron donating effects of pushing groups may serve as a guide for preparation of nitrile superbases.…”
Section: Series Of Brønsted Organic Nitrogen Superbases With Known Ex...mentioning
confidence: 99%
See 1 more Smart Citation